Hydrocephalus - Hadi Soekma Siregar; Ridwan M. Daulay; Lily Emsyah; Bistok Saing (Paediatrica Indonesiana, 1988)
A retrospective study had been done, to find out the incidence of hydrocephalus during 1984-1985 in the Pediatric Neurology Sub Division of the Child Health Department Medical Faculty University of North Sumatera/Pirngadi Hospital Medan. The number, age groups, causes and treatment were reviewed. The cases consist of 17 children, 9 males (52,09%) and 8 females (47,01%). Most of the patients 12 (70,58%) were found in the age group of 1 year or less, and the others 5 (29,42%) in the age group of more than 1 year. The youngest was 1 year of age and the oldest 3 1/2 years. Six cases were caused by congenital abnormalities, 1 case by meningitis and in 10 cases the probable cause was unknown. Conservative treatment had been given to all cases.